Analisis Laporan Pertanggungjawaban Realisasi Anggaran Pendapatan dan Belanja Desa di Kabupaten Biak Numfor - Maran, Laura Claudia Christine; Usman, Sarah; Lotte, Lucky Natalia A. (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Objectives: This study aims to determine the factors that are a weakness for the Village Government in making accountability reports for the realization of the APBDes in Biak Numfor Regency. Method: The research method used in this research is Descriptive Qualitative. The sampling techniques used are population and area sampling techniques. The data collection techniques used are based on primary and secondary data. Findings: Accountability of village financial reports depends on the level of understanding of the community and the competence of human resources owned by the village. Theoretical Contribution/Originality: This study can provide valuable insights for local governments, and the community that the importance to pay attention to and overseeing the accountability of village financial management carried out by the Village Government. This article highlights the importance of local governments being able to pay attention to factors that become weaknesses in the accountability report for the realization of village revenue and expenditure budgets in Biak Numfor Regency. Practical Implications: This study provides insights for the Local Government and the community so that it can be followed up by paying more attention and supervising village financial management up to the village financial accountability report conducted by the Village Government. Research Limitations: This research only focuses on accountability for the realization of APBDes implementation in Biak Numfor Regency.